ASSOCIATION BETWEEN ESTROGEN LEVELS WITH INTRAOCULAR PRESSURE IN PRIMARY OPEN ANGLE GLAUCOMA PATIENT: Oral Presentation - Observational Study - Resident - Rambe, Alvin; Sari, Masitha Dewi; Aldy, Fithria; Ashar, Taufik (Ophthalmologica Indonesiana, 2024)
Introduction & Objectives There are studies that state that estrogen deficiency can exacerbate visual disturbances in glaucoma patients. To determine the relationship between estrogen levels and intraocular pressure (IOP) in patients with POAG. Methods This study used a case-control design in 30 POAG patients who came to the Ophthalmology Polyclinic at the University of North Sumatra Hospital and Network Hospital. The data collection method in this study used a consecutive sampling technique starting from February 2022 until the sample was filled. The inclusion criteria in this study were all women with POAG who were ?40 years old and willing to be the research sample. The exclusion criteria for this study were patients with a history of secondary glaucoma or a history of optic nerve disease, a history of ocular surgery (except cataracts), a history of orbital trauma, menstrual disorders, or currently on hormonal therapy, a history of systemic or autoimmune disease. Data is then collected and analyzed. Results Of the 30 patients with POAG, the majority were aged 45-65 years (46.7%) with an average age of 55.87(±12.91) years and had suffered from POAG for an average of 1.62(±2.08) years. The average patient had an intraocular pressure of 25.07(±6.12) mmHg, MD -12.99(±8.28) dB, VCDR 0.78(±0.13) mm, and estrogen levels 2.47(±2.11) pg/dL. There was no significant relationship between estrogen levels and intraocular pressure (p=0.851). Conclusion There was no significant association between estrogen levels and intraocular pressure in patients with POAG.